ISTIKHDĀM AL-KITĀB AL ‘ARABIYATI LĪ AL-NĀSYI'IN LI MAHMŪD ISMĀIL SHĪNĪ WA AL-ASHDIQĀ' FI TARQIYAT MAHĀRAT AL-LUGAT AL- ARABIYAT LADA AL-TULLĀBI FĪ AL-MADRASAT AL MUTAWASSITHAT AL-FAJAR MATARAM - Habiburrahman Habiburrahman; Nasarudin Nasarudin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
This study aims to investigate the development of students’ beliefs about learning Arabic in Intensive Arabic Course program at IAIN Palangka Raya across the educational backgrounds and gender. This study used a quantitative research approach by combining cross sectional and longitudinal research types. There are 214 (two hundred and fourteen) new students in Academic Year 2019 at IAIN Palangka Raya as participants of the study. Data were analyzed by using mean, independent sample test and ANOVA. The results showed that 1) the new students studying in the intensive Arabic course program had a strong belief about Arabic learning 2) there was no statistically significant difference between the students belief about Arabic learning across gender and the educational backgrounds at the beginning of the Intensive Arabic Course meeting, 3) there was no statistically significant difference between the students’ beliefs about Arabic learning across the educational backgrounds and the gender after the end of the Intensive Arabic course program, 4) there was no statistically significant difference in development of students' belief about learning Arabic between the beginning and the end of the Intensive Arabic Course program. Keywords: Arabic, beliefs about language learning, course, development